Homocysteine and cognitive function in the elderly - Pusparini, Pusparini (Universa Medicina, 2009)
Dementia is prevalent among elderly people, and projections show that the number of affected might triple over the next 50 years, because of a large increase in the oldest segment of the population. The objective of this study was to investigate the relationship between cognitive function and serum homocysteine level. This study was a cross-sectional study carried out in Mampang district, South Jakarta. A total of 94 elderly people was recruited for this study consisting of 44 females and 50 males. In this study serum homocysteine level was assessed by fluorescent polarization immunoassay and cognitive function with the mini mental state examination (MMSE). In elderly women MMSE scores for plasma homocysteine concentrations of <11.7 mmol/L, 11.7-14.9 mmol/L and >14.9 mmol/L were 24.00 ± 3.68, 23.80 ± 6.51, and 20.80 ± 9.00 respectively, with p=0.000. In elderly men the MMSE scores for plasma homocysteine concentrations of <11.7 mmol/L, 11.7-14.9 mmol/L and >14.9 mmol/L were respectively 27.66 ± 2.06, 26.33 ± 3.79 and 24.03 ± 5.52 with p=0.008. Homocysteine concentrations of >14.9 mmol/L were more commonly found in males (66%) than in females (22.70%). The results of a regression analysis indicated that the factors influencing cognitive function were level of education (p=0.001) and age (p=0.035), whereas gender and homocysteine concentration did not affect cognitive function (p=0.554 and p=0.714, respectively). Plasma homocysteine concentration was inversely related to cognitive function. The most important factors affecting cognitive function were level of education and age.